Reprogramming alternative macrophage polarization by GATM-mediated endogenous creatine synthesis: A potential target for HDM-induced asthma treatment - Yu, Li; Wang, Lingwei; Hu, Guang; Ren, Laibin; Qiu, Chen; Li, Shun; Zhou, Xiaohui; Chen, Shanze; Chen, Rongchang (Frontiers in Immunology, 2022)
Cellular energy metabolism plays a crucial role in the regulation of macrophage polarization and in the execution of immune functions. A recent study showed that Slc6a8-mediated creatine uptake from exogenous supplementation modulates macrophage polarization, yet little is known about the role of the de novo creatine de novobiosynthesis pathway in macrophage polarization. Here, we observed that glycine amidinotransferase (GATM), the rate-limiting enzyme for creatine synthesis, was upregulated in alternative (M2) polarized macrophages, and was dependent on the transcriptional factor STAT6, whereas GATM expression was suppressed in the classical polarized (M1) macrophage. Next, we revealed that exogenous creatine supplementation enhanced IL-4-induced M2 polarization, confirming recent work. Furthermore, we revealed that genetic ablation of GATM did not affect expression of M1 marker genes (Nos2, IL1b, IL12b) or the production of nitric oxide in both peritoneal macrophages (PMs) and bone marrow-derived macrophages (BMDMs). By contrast, expression levels of M2 markers (Arg1, Mrc1, Ccl17 and Retnla) were lower following GATM deletion. Moreover, we found that deletion of GATM in resident alveolar macrophages (AMs) significantly blocked M2 polarization but with no obvious effect on the number of cells in knockout mice. Lastly, an upregulation of GATM was found in lung tissue and bronchoalveolar lavage fluid macrophages from HDM-induced asthmatic mice. Our study uncovers a previously uncharacterized role for the de novo creatine biosynthesis enzyme GATM in M2 macrophage polarization, which may be involved in the pathogenesis of related inflammatory diseases such as an T helper 2 (Th2)-associated allergic asthma.